Swot Analysis in an Effort to Improve Competitive Strategies in the Service of Mahar Agung Organizer Services at PT. Maha Perkasa Indonesia - Supriya, Amanda; Kustini, Kustini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Event organizer service companies are increasingly showing their development from year to year. The increasing development of event organizer service companies is able to bring up competition between competitors in the field of event organizer services getting tighter. Increasingly fierce competition makes service companies in the field of event organizers try to improve strategies in competition. The purpose of this study was to determine the role of SWOT analysis in efforts to improve competitive strategies at Mahar Agung Organizer under PT Maha Perkasa Indonesia. This study used descriptive analysis methods, Internal Factor Evaluation (IFE Matrix), External Factor Evaluation (EFE Matrix), SWOT Matrix. The results of this study are shown from the IFE calculation of 3.3 and EFE of 3.71 which explains the company's position in quadrant I which can benefit the company with the most effective strategy implemented by the company is an aggressive strategy. The findings of this study indicate that the strategy competes by maximizing strengths and opportunities to continue to improve the company's progress.